Rotator cuff to deltoid and pectoralis tendon to anatomic neck distances: methods for anatomic restoration of humeral height and tuberosity position in proximal humerus fractures for operative fixation and arthroplasty - Cheah, Jonathan W. (JSES Int, 2020)
INTRODUCTION: Proper anatomic tuberosity reduction and restoration of humeral height during surgical treatment of proximal humerus fractures leads to fewer complications and better outcomes. In the presence of significant displacement and comminution in proximal humerus fractures, the assessment of the correct tuberosity position and humeral height can be challenging. The goal of this cadaveric study was to provide new and useful measurements for intraoperative guidance of proper tuberosity position and humeral height when treating proximal humerus fractures with open reduction internal fixation, anatomic hemiarthroplasty, or reverse total shoulder arthroplasty. METHODS: A total of 28 cadaveric shoulders were dissected with a deltopectoral approach. The distance between the insertion of the supraspinatus tendon and the superior aspect of the deltoid tendon was measured (cuff to deltoid distance [CDD]). Secondly, the distance between the superior aspects of the pectoralis major tendon to the medial aspect of the anatomic neck (PND) was measured. Further, we sought to determine if these measurements would correlate to patient height and differ between gender. RESULTS: The average age of the donors was 65.3 years (64% male). The CDD and PND were 87.6 ± 10.6 and 16.6 ± 6.9 mm, respectively (mean ± standard deviation). There were no differences between females and males for the CDD (86.9 ± 9.4 vs. 87.2 ± 15.2 mm, P = .96) and PND (16.3 ± 9.1 vs. 17.1 ± 5.9 mm, P = .76). There was no correlation between the cadaver height and CDD (R2 = 0.1) and PND (R2 = 0.3). DISCUSSION: In this study, we describe 2 new measurement tools that can readily be applied intraoperatively during surgical treatment of proximal humerus fractures to aid in tuberosity reduction and humeral height assessment. These measurements were found to be independent of patient height and gender and can be used as a reference tool for most patients.